2021
DOI: 10.1016/j.celrep.2021.109446
|View full text |Cite
|
Sign up to set email alerts
|

Multiple regulatory intrinsically disordered motifs control FOXO4 transcription factor binding and function

Abstract: Highlights d The interaction network between FOXO4 and b-catenin is deciphered d FOXO4 autoinhibition interferes with DNA binding and is counteracted by b-catenin d FOXO4 exists in multiple conformations regulated by phosphorylation and co-factors d ICAT switches between FOXO4 and TCF/LEF transcription factors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 96 publications
(108 reference statements)
0
32
0
Order By: Relevance
“…We identified regions in FOXO FH domains that differ in terms of their dynamics, and we determined that these differences are due to slight variations in amino acid sequence. Furthermore, we show that the intra-molecular interactions between the FH and transactivation domains (TADs) recently discovered in FOXO3 and FOXO4 ( Bourgeois et al., 2021 ; Kim et al., 2021 ; Wang et al., 2008 ) are also conserved in FOXO1 and FOXO6. Strikingly, we found that these interactions take place between FH domains and TADs of different FOXOs, provide the possibility of heterodimeric interaction with putative biological function.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…We identified regions in FOXO FH domains that differ in terms of their dynamics, and we determined that these differences are due to slight variations in amino acid sequence. Furthermore, we show that the intra-molecular interactions between the FH and transactivation domains (TADs) recently discovered in FOXO3 and FOXO4 ( Bourgeois et al., 2021 ; Kim et al., 2021 ; Wang et al., 2008 ) are also conserved in FOXO1 and FOXO6. Strikingly, we found that these interactions take place between FH domains and TADs of different FOXOs, provide the possibility of heterodimeric interaction with putative biological function.…”
Section: Introductionmentioning
confidence: 76%
“…The FH domains harbor a conserved N-terminal Trp-Gly motif that is especially affected in FOXO1, FOXO4 and FOXO6 upon binding to the CR3. These residues have been previously shown to be involved in intramolecular interactions in FOXO3 and FOXO4 ( Bourgeois et al., 2021 ; Wang et al., 2008 ). Interestingly, in FOXO3 binding of the CR3 to the FH domain cause only weak chemical shift perturbations in this region, indicating a weaker binding.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations